Pyrolysis Characteristics and Heat Transfer for Oil Shale and Oil Sand Retorting - Li, Ruixuan (Journal of Theory and Practice of Engineering Science, 2023)
In this paper, the properties of oil shale and oil sand were evaluated, including Fischer assay, proximate analysis, heat value, ultimate analysis, composition of retorting gas, et al.The pyrolysis experiments on Indonesia oil sand, Estonia and Longkou oil shale, were performed using the differential scanning calorimetry (DSC) and the thermogravimetric analyzer (TGA) at different heating rates of 15, 20, 25 and 30℃/min. The kinetic parameters (apparent activation energy E and frequency factor A) were determined using Friedman procedure, parallel pyrolysis reaction model and maximum pyrolysis rate method, respectively. It is found that the activation energy increases with the increasing conversion. The calculated results using parallel pyrolysis reaction model are shown to be in good agreement with experimental results. More than 50% reactions were carried out corresponding to the activation energy of 167~210 kJ·mol-1. The apparent activation energy in maximum pyrolysis rate was obtained, which is closed to the result of Friedman method corresponding to about conversion of 50%. It is also shown that the plot of lnA vs. E for oil sand and oil shale pyrolysis becomes a linear line.